Strategy for Conflict Completing of the Confirmation of Regional Borders Between the Niacoten II Village and Administrative Village Kuanino in East Nusa Tenggara Province - Fitratul Imam Leparatu; Kusworo Kusworo; Irwan Thahir (Institut Pemerintahan Dalam Negeri (IPDN), 2018)
The results showed vertical and horizontal conflict. There are some factors that causethese conflict such as history, cultures, religion, and education factor. Conflictcompletion effort that made by the government through some forms that put forwardby Huug Miall in Alimudin (2006: 49-54) namely negotiation, mediation, conciliation,problem-solving, and reconciliation. However, these efforts could not find an exactway out yet in terms of conflict resolution. Regarding to SWOT analysis results andLitmus Test, researcher obtained several strategies such as find out the roots fromterritorial boundaries conflict completion and resolve with tradition/culturesapproaches and religion, gives guarantee and prioritize in terms of societyadministration services, implementing The Ministry of Home Affairs Regulation No.45/2016 concerning Guidelines for Affirmation and Determination of VillageBoundaries. This territorial boundaries conflict affirmation has occurred since 2016,that is why the government should pay more attention with this issue and it is crucialto conduct an effort with minimizing factors that cause this conflict so that it could notgrowing widely. In terms of the strategies to solve territorial boundaries conflictcompletion, the continuing effort is important in order to solve territorial boundariesconflict completion through deeper approaches and persuasive with society. Asanother effort of conflict completion of territorial boundaries, through this study,researcher offering some strategies that can be used to find out the main problem thatcausing the occurrence of this conflict and resolving with social approaches andreligion. Moreover, the government should give guarantee towards theimplementation about the administration services of society after the determinationabout territorial boundaries, implementing decisive regulation about territorialboundaries namely The Ministry of Home Affairs Regulation No. 45/2016 concerningGuidelines for Affirmation and Determination of Village Boundaries.